2022
DOI: 10.1186/s12889-022-14202-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccines effectiveness against symptomatic SARS-CoV-2 during Delta variant surge: a preliminary assessment from a case-control study in St. Petersburg, Russia

Abstract: Background Studies of mRNA and vector-based vaccines used in different countries report acceptable levels of effectiveness against SARS-CoV-2 infection caused by the Delta variants of SARS-CoV-2. No studies estimated vaccine effectiveness (VE) of Gam-COVID-Vac and other vaccines used in Russia against symptomatic infection with Delta variant. In this population-based case-control study, we aimed to estimate the effectiveness of the Russian COVID-19 vaccines against symptomatic SARS-CoV-2 during… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The St. Petersburg city government offered this free service during the COVID-19 pandemic to all citizens of the city who experienced symptoms and had confirmed or suspected SARS-CoV-2 infection. This setting has been previously used to assess VE against referral to the hospitalisation in August 2021 and against symptomatic SARS-CoV-2 infection in October 2021 [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The St. Petersburg city government offered this free service during the COVID-19 pandemic to all citizens of the city who experienced symptoms and had confirmed or suspected SARS-CoV-2 infection. This setting has been previously used to assess VE against referral to the hospitalisation in August 2021 and against symptomatic SARS-CoV-2 infection in October 2021 [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, several subsequent effectiveness reports suggested that Gam-COVID-Vac remained highly effective during subsequent SARS-CoV-2 surges, including Delta variant of concern (VOC) [ 5 , 9 ]. The most recent report from St. Petersburg showed that in contrast to Gam-COVID-Vac, two other vaccines used in Russia, EpiVacCorona and CoviVac, were not similarly effective against symptomatic infection during the SARS-CoV-2 Delta VOC surge [ 10 ]. However, both vaccines were relatively rarely used compared to Gam-COVID-Vac, and the study was underpowered to detect their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the non-neutralizing immune response might have different changing dynamics over time. For example, despite the reduction in the neutralizing activity, the Sputnik V vaccine remains effective against hospitalization and severe lung injury associated with SARS-CoV-2 Omicron [ 22 , 23 ], which probably might be explained by the retention of activity of the effector links of the immunity. In the current study, we performed a functional characterization of anti-SARS-CoV-2 antibodies against Delta and Omicron variants after vaccination with Sputnik V. We aimed to assess the differences in reduction in neutralizing and Fc-mediated activity of vaccine sera for up to 6 months against B.1.617.2 (Delta) and B.A1.…”
Section: Introductionmentioning
confidence: 99%